Myosteatosis as a novel predictor of urinary incontinence after robot‐assisted radical prostatectomy. (17th September 2021) - Yamashita, Shimpei; Kawabata, Hiroki; Deguchi, Ryusuke; Ueda, Yuko; Higuchi, Masatoshi; Muraoka, Satoshi; Koike, Hiroyuki; Kikkawa, Kazuro; Kohjimoto, Yasuo; Hara, Isao
Abstract : Objectives: To evaluate the impact of sarcopenia and myosteatosis on urinary incontinence after prostatectomy. Methods: We retrospectively reviewed consecutive patients who underwent robot‐assisted radical prostatectomy without nerve sparing between December 2012 and March 2019. Psoas muscle index and average total psoas density, which were measured on preoperative computed tomography images at level L3, were used to evaluate sarcopenia and myosteatosis, respectively. In addition, several magnetic resonance imaging variables associated with pelvic muscles, the urethra and the prostate were measured. Urinary continence was defined as non‐use or use of just one incontinence pad per day. Logistic regression analyses aimed to identify the predictors of urinary incontinence 3 and 12 months after surgery. Results: Overall, 121 patients were included in the analysis. The incidence rates of urinary incontinence 3 and 12 months after surgery were 42% (51/121 cases) and 16% (19/121 cases), respectively. Logistic multivariable analysis showed that low average total psoas density was the only significant independent predictor of urinary incontinence 3 months after surgery ( P  < 0.01), and low obturator internus muscle thickness ( P  = 0.01), short membranous urethral length ( P  = 0.01) and low average total psoas density ( P  < 0.01) were significant independent predictors of urinary incontinence 12 months after surgery. By contrast, psoas muscle index was not statistically associated with urinary incontinence after surgery. Conclusions: Myosteatosis (low average total psoas density) could be a novel predictor of urinary incontinence after robot‐assisted radical prostatectomy.